QARAQALPAQ HÁM INGLIS TILINDEGI XALÍQ NAQÍL-MAQALLARÍNDA AT(HORSE) ZOONIMINIŃ QOLLANÍLÍWÍ - Mnajatdinova, Nargiza Aynatdin qızı; Amaniyazov, Allayar Oralbaevich (SCIENCE and SOCIETY, 2026)
The article examines the lexicon of zoonyms (animal names) used in Karakalpak and English folk proverbs and sayings. The research in the article is based on comparative, linguacultural, and semantic analysis methods. According to the research results, in Karakalpak folk proverbs, the lexicon of the horse zoonym reveals positive images such as courage, agility, friendship, and wealth, while in English proverbs, it is also used to depict images of friendship, military strength, wealth, health, and hard work. However, in a small number of English proverbs, the noun zoonym also denotes stubbornness and selfishness. Through this depiction, the speaker sharpens their thoughts and deeply reveals them symbolically.